Growth and Physiological Responses of Phaseolus Species to Salinity Stress. (20th September 2012) - Bayuelo-Jiménez, J. S.; Jasso-Plata, N.; Ochoa, I.
Abstract : This paper reports the changes on growth, photosynthesis, water relations, soluble carbohydrate, and ion accumulation, for two salt-tolerant and two salt-sensitive Phaseolus species grown under increasing salinity (0, 60 and 90 mM NaCl). After 20 days exposure to salt, biomass was reduced in all species to a similar extent (about 56%), with the effect of salinity on relative growth rate (RGR) confined largely to the first week. RGR of salt-tolerant species was reduced by salinity due to leaf area ratio (LAR) reduction rather than a decline in photosynthetic capacity, whereas unit leaf rate and LAR were the key factors in determining RGR on salt-sensitive species. Photosynthetic rate and stomatal conductance decreased gradually with salinity, showing significant reductions only in salt-sensitive species at the highest salt level. There was little difference between species in the effect of salinity on water relations, as indicated by their positive turgor. Osmotic adjustment occurred in all species and depended on higher K +, Na +, and Cl − accumulation. Despite some changes in soluble carbohydrate accumulation induced by salt stress, no consistent contributions in osmotic adjustment could be found in this study. Therefore, we suggest that tolerance to salt stress is largely unrelated to carbohydrate accumulation in Phaseolus species.